Pengambilan Keputusan dalam Konsumsi Sayuran dan Pola Konsumsi Pangan Petani Padi di Kecamatan Pugung Kabupaten Tanggamus - Wuryaningsih Dwi Sayekti; Begem Viantimala; Oktin Lefiana; Tyas Sekartiara Syafani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2021)
The study is to determine the decision making process in vegetable consumption, food consumption patterns, and vegetable consumption patterns of rice farmers households. This research is conducted using a survey method, the location is determined in Rantau Tijang Village, Pugung Subdistrict, Tanggamus Regency. The number of sample are 74 households which housewives are as respondent. Proportional random method is used as sampling technique. Data collection is carried out in July 2018. Data is analyzed qualitatively and statistically descriptive. The results showed that households in consuming vegetables through the stages of need recognition, information search, alternative evaluation, consumption process, and post-consumption evaluation. The highest consumption of household’s food consumption pattern of rice farmers (kg/household/week) were rice (grains), palm oil (oil and fat), and tempe (nuts). The highest frequency consumption are rice, seasoned vegetables (onion, garlic, chilies), and tempe. The highest amount of vegetable consumption was long beans and cucumber was the highest frequency of vegetables consumption. The most households get vegetables by buying and stir fry was the most common way of cooking by households. The average of household energy consumption is 6,896,05 kcal/day with an energy sufficiency level of 84.13 percent and Desirable Dietary Pattern (DDP) score is 71.86. Key words: consumption pattern, decision making, vegatables